2015
DOI: 10.3109/13697137.2015.1020484
|View full text |Cite
|
Sign up to set email alerts
|

Long-term health consequences of premature or early menopause and considerations for management

Abstract: Aim To review the current evidence concerning the long-term harmful effects of premature or early menopause, and to discuss some of the clinical implications. Material and methods Narrative review of the literature. Results Women undergoing premature or early menopause, either following bilateral salpingo-oophorectomy or because of primary ovarian insufficiency, experience the early loss of estrogen and other ovarian hormones. The long-term consequences of premature or early menopause include adverse effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
258
0
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(285 citation statements)
references
References 102 publications
(110 reference statements)
1
258
0
14
Order By: Relevance
“…Associated estrogen deficiency symptoms may also affect quality of life. These adverse outcomes have also been reported in young women with secondary POI due to bilateral oophorectomy [7], with outcome reports including overall acceleration of the aging process [8]. Although guidelines recommend continuous use of hormone therapy (HT) until the average age of menopause [2 9], studies show a mean duration of about one year [10].…”
Section: Introductionmentioning
confidence: 99%
“…Associated estrogen deficiency symptoms may also affect quality of life. These adverse outcomes have also been reported in young women with secondary POI due to bilateral oophorectomy [7], with outcome reports including overall acceleration of the aging process [8]. Although guidelines recommend continuous use of hormone therapy (HT) until the average age of menopause [2 9], studies show a mean duration of about one year [10].…”
Section: Introductionmentioning
confidence: 99%
“…Our results may provide essential information for understanding how hyperphosphorylated Tau accumulation, resulting from aging and OVX, is related to the associative learning loss that occurs in both women (Faubion et al 2015) and rats (Espinosa-Raya et al 2011) after the decline in ovarian activity.…”
Section: Introductionmentioning
confidence: 89%
“…In this sense, several studies have shown that loss of ovaries due to an oophorectomy in premenopausal women enhance the risk of several disorders typically associated to menopause stage which includes an increase in depression, anxiety and several types of memory disorders (Rocca et al 2007;Ðoković et al 2015;Faubion et al 2015). In the search of new approaches for alleviating the above symptoms, the removal of ovaries in rats has been proposed as a model for studying several disorders associated to human menopause (Li and Satinoff 1996) including those related with the loss of memory (Carroll et al 2010;Espinosa-Raya et al 2011;Ortiz-Pérez et al 2016;Wallace et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…There is minimal absorption of low-dose vaginal estrogen, with levels within normal postmenopausal levels. Based on 1-year safety studies, progestogen is not needed with low-dose vaginal estrogen 13 .…”
Section: Women With Only Vaginal Symptomsmentioning
confidence: 99%